Molecular Detection of the mecA and some Virulence Determinants in Methicillin-Resistant Staphylococcus aureus - Khalil, Wed L.; Al-Hayanni, Huda S. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Methicillin Resistant Staphylococcus aureus (MRSA) is globally acknowledged as a prominent contributor to both hospital-acquired and community infections. Understanding key virulence factors including coagulase production, hemolysis ability and biofilm formation, is crucial.Objective: The study aimed to establish a molecular characterisation of mecA gene and virulence factors genes (hla, icaA, and coa) in clinical isolates of MRSA obtained from two hospitals in Baghdad.Methods: A hundred and five isolates were obtained from clinical sources from November 2022 to March 2023 and their antibiotic sensitivity was assessed using the agar diffusion test against seven different antibiotics (Azithromycin, Ciprofloxacin, Nitrofurantoin, Rifampin, Trimethoprim, Ofloxacin and Oxacillin), Through Conventional Polymerase Chain Reaction, the presence of virulence factor genes including mecA, hla, icaA, and coa, was determined in MRSA isolates.Results: All MRSA isolates (100%) harboured the mecA, hla, and icaA genes while the coa gene was recognized in 50% of the isolates. Regarding antibiotic susceptibility, all MRSA isolates (100%) demonstrated sensitivity to Nitrofurantoin. Additionally, 96.8% of the isolates were sensitive to Oxacillin.Conclusion: Molecular detection of methicillin resistance genes and virulence genes can be used to diagnose MRSA isolates in hospitals. The presence of these genes may affect their pattern of sensitivity to antibiotics.